Fuel Consumption Pattern of Tractor-Implement Systems at Part Loads under Different Field Conditions - Goyal, S K; Mani, Indra; Singh, Upendra; Verma, M R (Journal of Agricultural Engineering, 2006)
Fuel economy and work performance of three different tractor models was determined at part loads with commonly used tillage implements in sandy loam soil at 15-17% moisture content under three soil cover conditions of stubbled, unploughed and tilled irrigated. Field experiment were conducted on tractor implement system using disc harrow and cultivator, at 1/3rd , 2/3rd and full speed control positions of the tractor engine. Three tractor models with their power rating of 30, 35 and 55 hp were used for experimentations under actual field conditions. Fuel consumption, field capacity, width and depth of cut of implements were measured at different part loads for different implements. The 1/3rd load setting was not found suitable keeping in view the very low field capacity. The 30 and 35 hp tractors required 15-17% more fuel in tilled irrigated soil conditions compared to other soil conditions whereas the same was almost similar in case of 55 hp tractor at 2/3rd and full load condition. In tilled irrigated soil tractor implement system of different models consumed an average of 3.73 L/h in case of cultivator and 3.3 L/h for disc harrow at 2/3rd throttle position. When compared with full load condition, 21.21% and 29.58% less fuel consumption were observed at 2/3rd load in case of disc harrow and cultivator, respectively.